2018
DOI: 10.1038/s41598-018-31689-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic domain walls as broadband spin wave and elastic magnetisation wave emitters

Abstract: We report on the direct observation of spin wave and elastic wave emission from magnetic domain walls in ferromagnetic thin films. Driven by alternating homogeneous magnetic fields the magnetic domain walls act as coherent magnetisation wave sources. Directional and low damped elastic waves below and above the ferromagnetic resonance are excited. The wave vector of the magnetoelastically induced acoustic waves is tuned by varying the excitation frequency. The occurrence of elastic wave emission is proved by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
(39 reference statements)
0
17
0
1
Order By: Relevance
“…It has been shown that local magnetic formations such as domain walls [45][46][47], edge bound demagnetizing fields [33,48,49], or vortices [23,24,50] can function as spin wave emitters offering effective "antenna" widths well below 200 nm. A major advantage of this approach is that the devices providing such formations are a lot larger than these effective widths.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that local magnetic formations such as domain walls [45][46][47], edge bound demagnetizing fields [33,48,49], or vortices [23,24,50] can function as spin wave emitters offering effective "antenna" widths well below 200 nm. A major advantage of this approach is that the devices providing such formations are a lot larger than these effective widths.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, nanoscale spin textures in magnetic materials have gained attention for their potential as functional elements in spin‐wave devices. In particular, spin‐wave guiding, generation, and tunable transmission were observed at naturally occurring spin textures such as vortices and domain walls.…”
mentioning
confidence: 99%
“…All the experiments in the references listed here so far were based on a laser-scanning approach, where the spatial profile of magnons is acquired by moving the sample with respect to a focused laser. In a recent work Holländer and coworkers [207] could observe magnons emitted from magnetic domain walls [208] using a wide-field Kerr microscopy, as shown in Fig. 14(a) using a picosecond laser system synchronized to a CCD camera as described in detail in Ref.…”
Section: Time Resolved Magneto-optical Kerr Effectmentioning
confidence: 99%